Role of Supply Chain Management in Quality of Healthcare Services - Chauhan , Poonam; Nagappa , A.N. (International Journal of Membrane Science and Technology, 2023)
Healthcare organizations in Haryana (Kurukshetra) face many supply chain management challenges that can be addressed through effective operational and management decisions. The aim of this paper is to examine the supply chain management of healthcare quality in developing countries, particularly in rural healthcare in Haryana (Kurukshetra), and to consider demographic variables such as gender, age, education level and healthcare experience. Design and Hypothesis Testing Approach Distributed 500 questionnaires to determine the impact of aspects of supply chain management on the quality of health services. 27 of his seven procurement officers and administrative staff in Kurukshetra Haryana. The primary method was to collect data from 73 rural health managers and procurement managers to identify the quality and size of health services. The results of our study show that a combination of timely delivery of health products, specifications, level of health product providers and safety in the rural health sector of Haryana (Kurukshetra) is related to the quality of health services. The scope of this article focuses on employing appropriate human resources and highly trained professionals in supply chain departments to improve the quality of health services in the supply chain. As a practical contribution, this article can help healthcare supply chain managers and organizations do their jobs better or create a competitive advantage by addressing the issues and challenges facing individual healthcare managers, organizations and their partners.